PERAN PASTORAL KONSELING KRISTEN DI TENGAH KRISIS PANDEMI COVID-19 - Farno Billy Arthur Gerung; Hesky Charles Opit (POIMEN Jurnal Pastoral Konseling, 2020)
ABSTRACT At present the covid19 virus dominates life on earth, so that many experience problems of the quick and ultimately experience crisis problems and these crises cover various fields of human life. The various problems that cause this crisis make each counselor must be prepared to deal with what is happening around him, because this crisis problem is very extreme to one's personal life and if the counselor is not observant and adept at handling this crisis problem then those who experience this crisis will experience a bad life , so that each counselor must prepare and equip with a variety of existing knowledge. Various methods must be considered by each counselor so he can know with certainty the right way to handle the case at hand, at least the method of phenomenology that accelerates to know the situation that occurs. If everything is known and equipped with all the materials or equipment needed then as a counselor is ready to carry out the pastoral counseling process based on the word of God.